Intermolecular Ketene–Alkene [2+2] Cycloadditions: The Significance of Lewis Acid Promoted Variants - Rasik, Christopher M.; Brown, M. Kevin (Synlett, 2014)
Ketene–alkene [2+2] cycloadditions are an important class of reactions for chemical synthesis. These processes were exclusively carried out under thermal conditions, which ultimately lead to limitations regarding scope and stereoselectivity. Reviewed herein are recently developed Lewis acid promoted ketene–alkene [2+2] cycloadditions that address several of the problems known to plague these reactions.
Keywords: stereoselective synthesis; Lewis acids; cycloaddition; aluminum; alkenes